2011
DOI: 10.1007/s12298-011-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selenium and other micronutrients on the antioxidant activities and yield of corn (Zea mays L.) under drought stress

Abstract: The effects of selenium (Se) on plant growth under drought stress and in the presence of micronutrients are yet to be investigated. Hence, in a field experiment in 2007 the effects of Se and micronutrients including iron (Fe), zinc (Zn), copper (Cu), manganese (Mn), boron (B) and molybdenum (Mo) were evaluated on corn (Zea mays L.) grain yield under drought stress. Main-and sub-plots were devoted to irrigation (control and water stressed at the eight-leaf, blister and grain filling stages) and micronutrients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 28 publications
1
32
0
2
Order By: Relevance
“…The homogenates were centrifuged at 15,000×g and 4°C for 20 min, and the supernatants were used for assaying enzyme activity [53]. …”
Section: Methodsmentioning
confidence: 99%
“…The homogenates were centrifuged at 15,000×g and 4°C for 20 min, and the supernatants were used for assaying enzyme activity [53]. …”
Section: Methodsmentioning
confidence: 99%
“…Foliarly-applied Se also increased the respiratory potential in young chicory plants [14]. Addition of Se significantly enhanced the antioxidant activity, antioxidant level and maize grain yield when drought stress level was increased [36].…”
Section: Discussionmentioning
confidence: 89%
“…The method of the DPPH free radical, a stable organic free radical, is widely used for a rapid evaluation of the antioxidant activity of specific compounds or extracts. Sajedi et al . reported that the application of Se significantly increased the antioxidant activity and yield of maize, whereas Chu et al .…”
Section: Discussionmentioning
confidence: 99%
“…NS, no significant difference at P < 0.05. specific compounds or extracts. Sajedi et al 28 reported that the application of Se significantly increased the antioxidant activity and yield of maize, whereas Chu et al 12 found that the H 2 O 2 concentration was significantly reduced with spraying of Se at the later stage of wheat growth, although no difference was observed with spraying of Se at the early stage of wheat growth. In the present study, spraying foliar selenate or selenite showed no significant effect on the DPPH free radical scavenging rate of the two blueberry cultivars.…”
Section: Effects Of Se Spray On Conventional Quality and Storage Of Bmentioning
confidence: 99%